MODEL DESAIN LANSEKAP RUANG TERBUKA PUBLIK PADA ERA NEW NORMAL DI PERMUKIMAN PESISIR KOTA KENDARI (STUDI KASUS : PERMUKIMAN PESISIR KELURAHAN TONDONGGEU) - Ainussalbi Al Ikhsan; La Ode Amrul Hasan; Weko Indira Romantiaulia; Abdi Juryan Ladianto (Jurnal Malige Arsitektur, 2020)
Tondonggeu is a village located in Nambo District, Kendari City, a coastal settlement area with moderate density. The land use in the coastal settlement area of Tondonggeu Village is dominated by house buildings that grow linearly following the boundary line of the tide. Along with its development, the level of building density is higher and reduces the area of open space. The availability of open space in the coastal settlement of Tondonggeu does not have a good quantity and quality as a communal space that can be used by the community to socialize, interact, or carry out other public activities. The purpose of this research is to identify the forms of public open space that exist in the residential area of Tondonggeu. Qualitative research methods were used in this research and experimental methods were used to obtain a suitable landscape design model which later became the direction for the development of the coastal settlement area of Tondonggeu village and the coastal settlement area of Kendari City in general. The results of this study indicate that the form of public open space in the waterfront settlement area of Tondonggeu Village is linear and square.open space Square in residential areas in the form of yards of public and social facilities owned by the government which are used spontaneously without any special arrangement. For open spaces that are linear in the form of an environmental road which functions as a circulation space and an open space for society. The use of this open space is due to the limited public spaces that are square / plaza in nature. Under the category of open spaces in Tondonggeu residential areas included in the public space scale environment with a spacious and scope of small service in the form of space around the dwelling(home oriented space),the open space environment (neighborhood space)